Exploration of Japanese Language Learning Models In The Implementation of The Independent Curriculum In SMA/SMK - Widianti, Susi; Kusrini, Dewi; Dewanty, Via Luviana; Sutedi, Dedi; Hayati, Novia (Dimasatra, 2023)
The purpose of this study is to provide opportunities for teachers to gain, strengthen and increase knowledge and experience about online-based Japanese language learning models, explore online-based Japanese language learning models that can be used in their classroom contexts and apply learning models Japanese in their respective classes effectively. The target of this activity is Japanese language teachers at the SMA/SMK/MA level throughout Indonesia. This activity was carried out online through three webinars which were mapped into three stages. The first stage is the distribution of questionnaires containing questions regarding experiences of exploring and using online-based learning models before being given training. This stage was not carried out via webinar but was collected via a Google form which was sent to the participants. The data was processed to obtain their background regarding their experience of using online-based Japanese language learning models in their respective schools. The second stage included two webinars that presented presentations and simulations from experts and practitioners of online-based Japanese language learning models, especially in teaching letters, vocabulary, grammar and skills including listening, reading, writing and speaking. The final stage is practice in the form of a simulation for the participants in using online-based Japanese language learning models which have been presented in two webinars. At the end of the activity, a questionnaire containing questions about experiences and impressions of using online-based learning models after training will be distributed. Through this training activity, it is hoped that Japanese language teachers in Indonesia can apply existing online-based learning models effectively so that the predetermined learning competencies can be achieved and students become competent in Japanese.